Differences in the toxicity of cerium dioxide nanomaterials after inhalation can be explained by lung deposition, animal species and nanoforms. (3rd July 2018) - Dekkers, Susan; Ma-Hock, Lan; Lynch, Iseult; Russ, Mike; Miller, Mark R.; Schins, Roel P. F.; Keller, Jana; Römer, Isabella; Küttler, Karin; Strauss, Volker; De Jong, Wim H.; Landsiedel, Robert; et al.
Abstract: Considerable differences in pulmonary responses have been observed in animals exposed to cerium dioxide nanoparticles via inhalation. These differences in pulmonary toxicity might be explained by differences in lung deposition, species susceptibility or physicochemical characteristics of the tested cerium dioxide nanoforms (i.e. same chemical substance, different size, shape, surface area or surface chemistry). In order to distinguish the relative importance of these different influencing factors, we performed a detailed analysis of the data from several inhalation studies with different exposure durations, species and nanoforms, namely published data on NM211 and NM212 (JRC repository), NanoAmor (commercially available) and our published and unpublished data on PROM (industry provided). Data were analyzed by comparing the observed pulmonary responses at similar external and internal dose levels. Our analyses confirm that rats are more sensitive to developing pulmonary inflammation compared to mice. The observed differences in responses do not result purely from differences in the delivered and retained doses (expressed in particle mass as well as surface area). In addition, the different nanoforms assessed showed differences in toxic potency likely due to differences in their physicochemical parameters. Primary particle and aggregate/agglomerate size distributions have a substantial impact on the deposited dose and consequently on the pulmonary response. However, in our evaluation size could not fully explain the difference observed in the analyzed studies indicating that the pulmonary response also depends on other physicochemical characteristics of the particles. It remains to be determined to what extent these findings can be generalized to other poorly soluble nanomaterials.